Pengembangan Agrowisata Berbasis Pertanian Ramah Lingkungan di Desa Plalangan, Kecamatan Kalisat, Kabupaten Jember - Iqbal Erdiansyah; Muhammad Dzulkifli; Agus Hariyanto; Khusnul Khotimah; Vemas Aditia; Eliyatiningsih Eliyatiningsih (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Plalangan Village, Kalisat Subdistrict, Jember Regency, East Java, is an agricultural village with significant potential in food crop production and fisheries that can be developed into agrotourism. However, this potential has not been optimally managed, particularly by Kelompok Sadar Wisata Selayang Pandang (Pokdarwis), whose role in tourism development remains limited. This community service programme aimed to increase Pokdarwis' knowledge and awareness of village tourism potential and to enhance skills related to environmentally friendly agricultural practices to support agrotourism development. The activities included a survey of tourism potential, socialisation, and training on environmentally friendly agriculture, conducted using a participatory approach involving all Pokdarwis members. The evaluation results showed an improvement in Pokdarwis's ability to identify village tourism potential and an increased understanding of environmentally friendly agriculture. This programme is expected to support the optimisation of village potential and contribute to the development of Plalangan Village as a sustainable agrotourism destination that improves community welfare.